Demographic study of congenital talipes equinovarus deformity in central India - Ahirwar, Rahul; Upadhyay, Sachin; Varma, H. S. (International Journal of Research in Medical Sciences, 2021)
Background: Congenital idiopathic clubfoot is the most common birth defect of the musculoskeletal system affecting 1 in every 1000 live births each year. Aim of our study was to determine the demographic variables, risk factors associated with CTEV in central India. Methods: A retrospective study was conducted from January 2019 to August 2020 using data of 200 patients with CTEV registered at department of orthopaedics, Netaji Subhash Chandra Bose medical college, Jabalpur, Madhya Pradesh, India were included in our study. Results; Out of total of 200 patients, 167 patients belong to age group <1 year (83.5%) with range from 10 days -7 years. Males were twice (65%) likely affected and (53.5%) clubfoot cases had both feet affected. Right side was more affected in unilateral cases. 189 patients (94.5%) were idiopathic, whereas 11 patients (5.5%) were non-idiopathic. there were 58 (29%) children out of 200, born of consanguineous marriage of parents. Risk factors like anemia, jaundice, asphyxia, obstructed labor, history of miscarriage had positive correlation with clubfoot. CTEV patients of low birth weight <2.5 kg associated with maternal risk factors like smoking, alcohol, anemia. Conclusions: Demographic study is useful tool for determining birth prevalence and risk factors associated with CTEV. There are significantly higher proportion of consanguinity in clubfoot patients. Cultural differences may lead to differences in our findings with respect to the previous studies. These preliminary findings will help in the future for similar studies in central India as well as in the general Indian population.